The theology of the Oral Torah : revealing the justice of God - Neusner, Jacob, 1932-2016 (McGill-Queen's studies in the history of religion., 1999)
"The Theology of the Oral Torah demonstrates the cogency and inner rationality of the classical statement of Judaism in the Oral Torah, bringing a theological assessment to bear on the whole of rabbinic literature. Jacob Neusner shows how the proposition that God is One and all-powerful but also merciful and just defines the system and structure of rabbinic Judaism. He argues that in working this proposition out in rich detail the classical texts generate the central rabbinic problem: how can the conflicting traits inherent in the proposition be resolved?"--Jacket